An Experimental Evaluation of an Online Interview Scheduler: Effects on Fieldwork Outcomes. (23rd October 2020) - McGonagle, Katherine; Sastry, Narayan
Abstract: In recent years, household surveys have expended significant effort to counter well-documented increases in direct refusals and greater difficulty contacting survey respondents. A substantial amount of fieldwork effort in panel surveys using telephone interviewing is devoted to the task of contacting the respondent to schedule the day and time of the interview. Higher fieldwork effort leads to greater costs and is associated with lower response rates. A new approach was experimentally evaluated in the 2017 wave of the Panel Study of Income Dynamics (PSID) Transition into Adulthood Supplement (TAS) that allowed a randomly selected subset of respondents to choose their own day and time of their telephone interview through the use of an online appointment scheduler. TAS is a nationally representative study of US young adults aged 18–28 years embedded within the worlds' longest running panel study, the PSID. This paper experimentally evaluates the effect of offering the online appointment scheduler on fieldwork outcomes, including number of interviewer contact attempts and interview sessions, number of days to complete the interview, and response rates. We describe panel study members' characteristics associated with uptake of the online scheduler and examine differences in the effectiveness of the treatment across subgroups. Finally, potential cost-savings of fieldwork effort due to the online appointment scheduler are evaluated.